Political Decision-making, Lottocracy, and AI - Slater, Joe (Conatus - Journal of Philosophy, 2025)
This article examines an argument for single-issue legislatures (SILs) as an alternative to typical decision-making procedures in representative democracies. It is argued that if this argument was successful, it could be extended to endorse decision-making processes utilizing advanced artificial intelligence. However, it is noted that this argument neglects an important feature of decision-making: authorization. It is important for its autonomy that a society must authorize certain decisions. If decisions were delegated to SILs or AI, this would undermine the autonomy of the group. This does not entail that these alternatives have no role in policy-crafting. It is argued that so long as a community can authorize a decision, perhaps by a vote, it need not undermine autonomy. An important caveat of this, however, is that the decision must be explicable to the community. For AI usage, this motivates the need for explainable AI (XAI).